Application Of The Total Physical Response Method In Learning English In Early Children - Aryani, Novia; Sitinjak, Lasmaria Tiodora Silviana; Tindaon, Cweeta Asty Ayu Zelita; Napitupulu, Febriana Monika (Generasi: Jurnal Pendidikan Anak Usia Dini, 2023)
This paper discusses the importance of applying the Total Physical Response (TPR) method in English learning for early childhood and highlights the crucial role of parents in supporting its implementation at home. TPR is a language teaching method that connects verbal input with physical movement, allowing children to acquire language naturally through action, imitation, and play. In early childhood education, TPR effectively enhances listening comprehension, vocabulary retention, and active participation, aligning with children’s holistic developmental characteristics physical, cognitive, social, and emotional. By reducing anxiety and increasing motivation, TPR creates a joyful and meaningful learning environment where children learn English through experience rather than memorization. English is used often in daily life and has a variety of uses, including in business, education, tourism, and health. Students' English proficiency needs to be raised because, being an international language, English is used in many sciences. Therefore, communicating well in English is advantageous, even in the workplace. In this instance, the proper approach is required to aid in developing and introducing English, especially in the early years. Total Physical Response (TPR) Method application in English Learning is one of the most appropriate and effective for being applied in teaching and learning process in the classroom. Total Physical Response (TPR) is one of the most suitable and relevant strategies for introducing an object in English language learning. The Total Physical Response (TPR) method encourages young children to learn English actively.